Functionalized aromatic heterocyclic block polyether ester-polyphenylene sulfide copolymer, preparation method thereof and PPS coating

By modifying polyphenylene sulfide from amino-terminated and copolymerizing with hydroxy-terminated aromatic heterocyclic block polyether ester, combined with nanofillers, a high toughness and excellent impact resistance PPS coating was prepared, which solved the flexibility of polyphenylene sulfide coating The problems of insufficient properties and poor processing performance have achieved better chemical corrosion resistance and bonding properties.

CN119463198AInactive Publication Date: 2025-02-18SUFU (SHENZHEN) TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510052098.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Polyphenylene sulfide coatings are not flexible enough in high temperature and corrosive environments, prone to cracking and peeling, and have poor processing performance.

Method used

Functional aromatic heterocyclic block polyether ether ether copolymer is prepared by amino-terminated modification of polyphenylene sulfide and copolymerized with hydroxy-terminated aromatic heterocyclic block polyether ether ester, and combined with nanofillers such as Modified graphene oxide to prepare PPS coating.

Benefits of technology

Improves the toughness, impact resistance, chemical corrosion resistance and bonding properties of the coating, while reducing viscosity, improving processing performance and cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of high-molecular copolymers, and particularly relates to a functionalized aromatic heterocyclic block polyether ester-polyphenylene sulfide copolymer, a preparation method thereof and a PPS coating, and the preparation method of the copolymer comprises the following steps: (1) preparing amino-terminated polyphenylene sulfide; (2) preparing hydroxyl-terminated aromatic heterocyclic block polyether ester; and (3) preparing the aromatic heterocyclic block polyether ester-polyphenylene sulfide copolymer. Compared with the prior art, the copolymer obtained by the invention is easy to process, and a coating layer formed by the paint has high toughness and impact resistance, excellent chemical corrosion resistance and adhesive property and lower cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of high molecular copolymers, and in particular relates to a functionalized aromatic heterocyclic block polyether ester-polyphenylene sulfide copolymer and a preparation method thereof and a PPS coating. Background Art

[0002] High-temperature anti-corrosion coatings refer to coatings that have long-term anti-corrosion properties under high temperature and harsh corrosive environments (acids, alkalis, etc.). Since it has to withstand high temperatures and corrosive environments at the same time, the requirements for materials are very high. Polyphenylene sulfide (PPS) is a high-performance thermoplastic resin, and the coating made with it as the main film-forming substance is PPS coating. It has excellent properties such as high temperature resistance, corrosion resistance, wear resistance, and good electrical insulation, and has broad application prospects in many industrial fields. PPS coatings can be used for a long time in high-temperature environments of about 200°C, and can even withstand higher temperatures in a short period of time. For example, in high-temperature working conditions such as some industrial furnaces, automobile engine parts, etc., the coating can still maintain good stability, and there will be no peeling, shedding, discoloration and other adverse phenomena caused by high temperatures.

[0003] However, the molecular chain of polyphenylene sulfide is relatively rigid, which results in poor flexibility of the coating after film formation. When subjected to external impact or bending deformation, the coating is prone to cracking and peeling, affecting its protective performance and service life. For example, coating polyphenylene sulfide on the surface of some parts that need to be bent or vibrated frequently may cause premature damage to the coating due to insufficient flexibility. In addition, polyphenylene sulfide has high viscosity and is difficult to process.

[0004] For example, CN100402617A discloses a polyphenylene sulfide epoxy composite high temperature resistant anticorrosive coating and its preparation method. The anticorrosive coating consists of a primer, a topcoat and an intermediate coating. The primer consists of polyphenylene sulfide, epoxy resin, glass flakes and dicyandiamide. The topcoat consists of polyphenylene sulfide, epoxy resin, corundum, 4,4'-diaminodiphenyl sulfone and dicyandiamide. The intermediate coating consists of polyphenylene sulfide, epoxy resin, graphite, corundum, glass flakes, sebacic acid dihydrazide and 4,4'-diaminodiphenyl sulfone. This application enhances its high temperature resistance and corrosion resistance by modifying epoxy resin with polyphenylene sulfide, but the resulting coating is prone to cracking and peeling.

[0005] For example, CN114989721A discloses a polyphenylene sulfide compound coating and its preparation method, coating method, and a polyphenylene sulfide coating with a smooth surface and no defects made therefrom, which belongs to the technical field of chemical coatings. The compound coating of the present invention comprises 97-99.5% polyphenylene sulfide and 0.5-3% nanofiller by weight percentage. The application reduces the dielectric constant by synergistically using fillers and polyphenylene sulfide, but the polyphenylene sulfide molecular chain is relatively rigid, the resulting polyphenylene sulfide coating is not flexible enough, and its processing performance still needs to be improved.

[0006] In view of this, the present invention is proposed. Summary of the invention

[0007] The purpose of the present invention is to provide a functionalized aromatic heterocyclic block polyether ester-polyphenylene sulfide copolymer and a preparation method thereof and a PPS coating. The copolymer obtained by the present invention is easy to process, and the coating formed by the coating has high toughness and impact resistance, excellent chemical corrosion resistance and bonding performance, and has lower cost.

[0008] In order to achieve the above object, the present invention provides the following technical solutions: In a first aspect, the present invention provides a method for preparing a functionalized aromatic heterocyclic block polyether ester-polyphenylene sulfide copolymer, comprising the following steps: (1) mixing a sulfur source, an alkali metal compound, a polymerization agent, an organic solvent and water to obtain a mixture, stirring and heating the mixture, then adding p-dichlorobenzene to polymerize, and then adding p-aminochlorobenzene to cap the mixture to obtain amino-capped polyphenylene sulfide; (2) under nitrogen protection, polyethylene glycol and 2,5-furandicarboxylic acid are mixed, and then tetraisopropyl titanate is added, and the temperature is raised to react to obtain a hydroxyl-terminated aromatic heterocyclic block polyether ester; (3) Under nitrogen protection, amino-terminated polyphenylene sulfide, hydroxyl-terminated polyether ester, tetrakistriphenylphosphine palladium, and toluene are mixed, and the pH is adjusted to 8-11 to obtain an aromatic heterocyclic block polyether ester-polyphenylene sulfide copolymer.

[0009] In a preferred embodiment, in step (1), the sulfur source is one or more of sodium hydrosulfide, sodium sulfide, and potassium sulfide.

[0010] In a preferred embodiment, in step (1), the alkali metal compound is sodium hydroxide.

[0011] In a preferred embodiment, in step (1), the organic solvent is n-methylpyrrolidone.

[0012] In a preferred embodiment, in step (1), the polymerization agent is sodium acetate.

[0013] In a preferred embodiment, in step (1), the equivalent ratio of the sulfur source to the alkali metal compound is 1:(0.8-1.5).

[0014] In a preferred embodiment, in step (1), the equivalent ratio of the sulfur source to the organic solvent is 1:(2-5), and the equivalent ratio of the organic solvent to water is 0.5:(0.85-1.5).

[0015] In a preferred embodiment, in step (1), the equivalent ratio of the sulfur source to the polymerization agent is 1:(0.02-0.07).

[0016] In a preferred embodiment, in step (1), the equivalent ratio of the sulfur source, p-dichlorobenzene and p-aminochlorobenzene is 1:(1.2-1.5):(0.3-0.6).

[0017] In a preferred embodiment, in step (1), the stirring and heating temperature is 150-190° C., and the stirring and heating time is 10-30 min.

[0018] In a preferred embodiment, in step (1), the polymerization temperature is 210-250° C., and the polymerization time is 2-4 hours.

[0019] In a preferred embodiment, in step (1), the end-capping temperature is 230-270° C., and the end-capping time is 0.5-1 h.

[0020] In a preferred embodiment, in step (2), the number average molecular weight of the polyethylene glycol is 200-2000.

[0021] In a preferred embodiment, in step (2), the mass ratio of the polyethylene glycol, 2,5-furandicarboxylic acid and tetraisopropyl titanate is 1:(0.8-1.5):(0.01-0.05).

[0022] In a preferred embodiment, in step (2), the temperature of the temperature-raising reaction is 180-260° C., and the time of the temperature-raising reaction is 2-5 h.

[0023] In a preferred embodiment, in step (3), the mass ratio of the amino-terminated polyphenylene sulfide, the hydroxy-terminated polyether ester, tetrakistriphenylphosphine palladium and toluene is 1: (1.2-1.5): (0.01-0.05): (1-10).

[0024] In a preferred embodiment, in step (3), the reaction temperature is 80-110° C., and the reaction time is 4-8 h.

[0025] In a second aspect, the present invention provides an aromatic heterocyclic block polyether ester-polyphenylene sulfide copolymer obtained by the preparation method of the functionalized aromatic heterocyclic block polyether ester-polyphenylene sulfide copolymer as described above.

[0026] In a third aspect, the present invention provides a PPS coating, which comprises the following components in terms of mass ratio: 100 parts of the above-mentioned aromatic heterocyclic block polyether ester-polyphenylene sulfide copolymer and 1-3 parts of nanofiller.

[0027] In a preferred embodiment, the nanofiller is modified graphene oxide, and the preparation method of the modified graphene oxide is as follows: The graphene oxide is dissolved in water, ultrasonicated for 1-2 hours, and then urea is added, wherein the mass ratio of urea to graphene oxide is (4-8):1, refluxed at 60-100°C for 0.5-1.5 hours, and the modified graphene oxide is obtained after washing and drying.

[0028] In a preferred embodiment, the particle size of the graphene oxide is 50-100 nm.

[0029] The present invention specifically limits the nanofiller to homemade amino-treated graphene oxide. Since the above-mentioned PPS coating contains amino groups, the nanofiller provided by the present invention has good compatibility with it, so the amino-treated graphene oxide is easier to disperse in the PPS coating, avoiding the occurrence of agglomeration, which is conducive to giving full play to the performance of graphene oxide. Graphene oxide itself has a two-dimensional sheet structure and can effectively block the penetration of gas and liquid. After amination, its dispersibility and interfacial bonding force in the matrix are further enhanced, which is more conducive to forming a dense barrier layer, thereby significantly improving the barrier performance of the coating and its chemical corrosion resistance. In addition, the amino-treated graphene oxide further reduces the viscosity of the PPS coating, improves its fluidity and coating properties, makes the coating easier to construct and operate, can better adapt to different coating processes and equipment, and improves production efficiency and coating quality.

[0030] Compared with the prior art, the advantages and beneficial effects of the present invention are: 1. The present invention improves the compatibility of polyphenylene sulfide, enhances the reaction activity of polyphenylene sulfide, improves the bonding performance of polyphenylene sulfide, increases the surface activity of polyphenylene sulfide and improves the processing performance of polyphenylene sulfide by amino-terminated polyphenylene sulfide.

[0031] Among them, polyphenylene sulfide is a crystalline polymer, which has high rigidity and heat resistance, but may have poor compatibility with other materials. Amino-terminated can introduce polar amino groups, increase the compatibility of polyphenylene sulfide with other polar polymers, inorganic fillers, etc., and thus make it easier to prepare high-performance composite materials. And the amino group has high reactivity and can participate in a variety of chemical reactions. This allows amino-terminated polyphenylene sulfide to react with compounds containing active groups such as carboxyl, hydroxyl, and epoxy groups, and further modify, crosslink or copolymerize polyphenylene sulfide, providing a reaction basis for subsequent polyetherester copolymerization. Furthermore, there is a certain interaction force between amino groups and the surfaces of many materials, such as hydrogen bonds, acid-base effects, etc. Therefore, when amino-terminated polyphenylene sulfide is used as a coating material, it can better combine with the surface of the bonded object and improve the bonding strength. In addition, the introduction of amino groups can increase the activity and hydrophilicity of the surface of polyphenylene sulfide, making it easier to carry out surface treatment and functionalization, laying the foundation for subsequent reactions. What's more, amino end-capping can reduce the melting point and melt viscosity of polyphenylene sulfide to a certain extent and improve its processing fluidity. This is beneficial to the filling and molding of polyphenylene sulfide during the molding process, reduces defects in the product, improves production efficiency and product quality, and makes it easier to prepare and process.

[0032] In addition, the present invention obtains a hydroxyl-terminated aromatic heterocyclic block polyether ester, more specifically a furan block polyether ester, by self-production. First, it has excellent shape memory function. When used to prepare a coating, its excellent shape memory function enables the coating formed by it to have good toughness and impact resistance. It also improves the mechanical strength, elasticity, heat resistance and chemical resistance of the polyether ester.

[0033] The present invention provides a heterocyclic block polyether ester-polyphenylene sulfide copolymer obtained by hydroxyl-terminated heterocyclic block polyether ester and amino-terminated polyphenylene sulfide. The copolymer has the excellent properties of both polyether ester and polyphenylene sulfide. More specifically, the copolymer has excellent toughness and impact resistance, good tensile properties, easy processing, and a wide operating temperature range.

[0034] Among them, polyphenylene sulfide itself is a relatively rigid polymer, and its molecular chain is regular and the rigid structure accounts for a large proportion. This makes it have high strength and hardness, but relatively poor toughness, and it is easy to crack when subjected to external force impact. Polyether ester has good flexibility, and the molecular chain contains relatively flexible segments such as ether bonds and ester bonds, which can give the material better elasticity and deformation ability. When polyether ester is blended or copolymerized with polyphenylene sulfide, the flexible segments of polyether ester can be interspersed between the rigid molecular chains of polyphenylene sulfide, playing a role similar to "buffering" and "isolation", effectively hindering the expansion of cracks, dispersing the energy generated by external force impact, thereby improving the toughness and impact resistance of the overall material. And the self-made aromatic heterocyclic block polyether ester of the present invention has an excellent shape memory function, which further strengthens this performance.

[0035] In terms of tensile properties, the flexibility of the polyetherester molecular chain enables it to deform to a large extent without breaking when subjected to tension. After mixing with polyphenylene sulfide, the molecular chains of the two are entangled and interact with each other. During the stretching process, the polyetherester chain segment first undergoes tensile deformation, sharing part of the tension, delaying the polyphenylene sulfide chain segment from reaching the limit strain and breaking, thereby optimizing the tensile performance indicators of the entire material, such as tensile strength and elongation at break, so that the material can maintain integrity under greater tension.

[0036] In terms of processing performance, polyphenylene sulfide has a high processing temperature and a large melt viscosity, which brings many inconveniences to the molding process. For example, in the process of injection molding and extrusion, high pressure and temperature are required, which is demanding on the processing equipment and is also prone to processing defects. The addition of polyether ester can reduce the melt viscosity of the entire system, improve the fluidity of the material, and make it easier to fill the mold cavity or pass through the die of the extruder during the processing, thereby reducing the temperature and pressure required for processing and molding, reducing energy consumption and wear on processing equipment, improving production efficiency and product quality, and facilitating the manufacture of products with complex shapes.

[0037] In terms of thermal properties, polyphenylene sulfide is a special polymer that is resistant to high temperatures and can maintain stable performance for a long time in high temperature environments. However, its low temperature performance is poor and it tends to become brittle under low temperature conditions, with a significant decrease in toughness and mechanical properties. Although polyether ester is not as resistant to high temperatures as polyphenylene sulfide, it also has a certain degree of thermal stability and can still maintain relatively good flexibility in low temperature environments. After the two are combined, the material can rely on polyphenylene sulfide to maintain structural and performance stability at high temperatures, and polyether ester can help maintain a certain degree of toughness at low temperatures, so that the overall material's operating temperature range is broadened and can adapt to more complex temperature change environments.

[0038] In terms of chemical resistance, polyphenylene sulfide itself has good chemical corrosion resistance and has good resistance to most acids, alkalis, organic solvents, etc. Although the ether bonds, ester bonds and other functional groups in polyether esters are slightly less resistant to some highly corrosive substances, they also give the material certain chemical resistance, and when synergistically acting with polyphenylene sulfide, the structure formed by the interweaving of the molecular chains of the two can prevent the penetration of chemical substances to a certain extent, further enhancing the overall material's tolerance to different chemical substances, allowing it to be used in harsher chemical environments.

[0039] 2. The present invention specifically limits the nanofiller to homemade amino-treated graphene oxide. Since the above-mentioned PPS coating contains amino groups, the nanofiller provided by the present invention has good compatibility with it, so the amino-treated graphene oxide is easier to disperse in the PPS coating, avoiding the occurrence of agglomeration, which is conducive to giving full play to the performance of graphene oxide. Graphene oxide itself has a two-dimensional sheet structure, which can effectively block the penetration of gas and liquid. After amination, its dispersibility and interfacial bonding force in the matrix are further enhanced, which is more conducive to forming a dense barrier layer, thereby significantly improving the barrier properties of the coating and its chemical corrosion resistance. In addition, the amino-treated graphene oxide further reduces the viscosity of the PPS coating, improves its fluidity and coating properties, makes the coating easier to construct and operate, and can better adapt to different coating processes and equipment, and improve production efficiency and coating quality. DETAILED DESCRIPTION

[0040] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] Unless otherwise specified, the reagents mentioned in this example are commercially available.

[0042] Example 1 This embodiment provides a method for preparing a functionalized aromatic heterocyclic block polyether ester-polyphenylene sulfide copolymer, comprising the following steps: (1) mixing sodium sulfide, sodium hydroxide, sodium acetate, n-methylpyrrolidone and water to obtain a mixture, wherein the equivalent ratio of sodium sulfide to sodium hydroxide is 1:1.2, the equivalent ratio of sodium sulfide to n-methylpyrrolidone is 1:4, the equivalent ratio of sodium sulfide to sodium acetate is 1:0.05, and the equivalent ratio of n-methylpyrrolidone to water is 0.5:1, stirring and heating at 170°C for 20 minutes, then adding p-dichlorobenzene for polymerization, the equivalent ratio of sodium sulfide to p-dichlorobenzene is 1:1.4, the polymerization temperature is 230°C, and the polymerization time is 3 hours, then adding p-aminochlorobenzene for end-capping, the equivalent ratio of sodium sulfide to p-aminochlorobenzene is 1:0.4, the end-capping temperature is 250°C, and the end-capping time is 1 hour, to obtain amino-terminated polyphenylene sulfide; (2) under nitrogen protection, polyethylene glycol (number average molecular weight of 400) and 2,5-furandicarboxylic acid were mixed, and then tetraisopropyl titanate was added, the mass ratio of polyethylene glycol, 2,5-furandicarboxylic acid and tetraisopropyl titanate was 1:1.3:0.03, and the mixture was reacted at 230°C for 4 seconds to obtain a hydroxyl-terminated aromatic heterocyclic block polyether ester; (3) Under nitrogen protection, amino-terminated polyphenylene sulfide, hydroxyl-terminated polyether ester, tetrakistriphenylphosphine palladium and toluene are mixed, wherein the mass ratio of amino-terminated polyphenylene sulfide, hydroxyl-terminated polyether ester, tetrakistriphenylphosphine palladium and toluene is 1:1.3:0.03:10, and then the pH is adjusted to 10. The reaction is carried out at 100° C. for 6 h to obtain an aromatic heterocyclic block polyether ester-polyphenylene sulfide copolymer.

[0043] Example 2 This embodiment provides a method for preparing a functionalized aromatic heterocyclic block polyether ester-polyphenylene sulfide copolymer, comprising the following steps: (1) mixing sodium sulfide, sodium hydroxide, sodium acetate, n-methylpyrrolidone and water to obtain a mixture, wherein the equivalent ratio of sodium sulfide to sodium hydroxide is 1:1.2, the equivalent ratio of sodium sulfide to n-methylpyrrolidone is 1:4, the equivalent ratio of sodium sulfide to sodium acetate is 1:0.05, and the equivalent ratio of n-methylpyrrolidone to water is 0.5:1, stirring and heating at 170°C for 20 minutes, then adding p-dichlorobenzene for polymerization, the equivalent ratio of sodium sulfide to p-dichlorobenzene is 1:1.4, the polymerization temperature is 230°C, and the polymerization time is 3 hours, then adding p-aminochlorobenzene for end-capping, the equivalent ratio of sodium sulfide to p-aminochlorobenzene is 1:0.4, the end-capping temperature is 250°C, and the end-capping time is 1 hour, to obtain amino-terminated polyphenylene sulfide; (2) under nitrogen protection, polyethylene glycol (number average molecular weight of 500) and 2,5-furandicarboxylic acid were mixed, and then tetraisopropyl titanate was added, the mass ratio of polyethylene glycol, 2,5-furandicarboxylic acid and tetraisopropyl titanate was 1:1.1:0.03, and the reaction was carried out at a temperature of 230°C for 4 seconds to obtain a hydroxyl-terminated aromatic heterocyclic block polyether ester; (3) Under nitrogen protection, amino-terminated polyphenylene sulfide, hydroxyl-terminated polyether ester, tetrakistriphenylphosphine palladium and toluene are mixed in a mass ratio of 1:1.4:0.03:10, and the pH is adjusted to 10. The reaction is carried out at 100° C. for 6 h to obtain an aromatic heterocyclic block polyether ester-polyphenylene sulfide copolymer.

[0044] Comparative Example 1 Compared with Example 1, the difference is that steps (2) and (3) are not performed.

[0045] Comparative Example 2 Compared with Example 1, the difference is that steps (1) and (3) are not performed.

[0046] Comparative Example 3 Compared with Example 1, the difference is that p-aminochlorobenzene is not added in step (1).

[0047] Comparative Example 4 Compared with Example 1, the difference is that in step (2), 2,5-furandicarboxylic acid is replaced by terephthalic acid.

[0048] Application Example 1 This application example provides a PPS coating, comprising 100 parts of the aromatic heterocyclic block polyether ester-polyphenylene sulfide copolymer prepared in Example 1, and 3 parts by weight of modified graphene oxide. The preparation method of the modified graphene oxide is as follows: Graphene oxide with a particle size of 60 nm was dissolved in water, ultrasonicated for 1 hour, and then urea was added, wherein the mass ratio of urea to graphene oxide was 6:1, refluxed at 90° C. for 1 hour, and the modified graphene oxide was obtained after washing and drying.

[0049] The two are mixed and stirred evenly to obtain the PPS coating.

[0050] Application Example 2 Compared with Application Example 1, the difference is that the aromatic heterocyclic block polyether ester-polyphenylene sulfide copolymer prepared in Example 1 is replaced by the aromatic heterocyclic block polyether ester-polyphenylene sulfide copolymer prepared in Example 2.

[0051] Application Example 3 Compared with Application Example 1, the difference is that the aromatic heterocyclic block polyether ester-polyphenylene sulfide copolymer prepared in Example 1 is replaced by the copolymer prepared in Comparative Example 1.

[0052] Application Example 4 Compared with Application Example 1, the difference is that the aromatic heterocyclic block polyether ester-polyphenylene sulfide copolymer prepared in Example 1 is replaced by the copolymer prepared in Comparative Example 2.

[0053] Application Example 5 Compared with Application Example 1, the difference is that the aromatic heterocyclic block polyether ester-polyphenylene sulfide copolymer prepared in Example 1 is replaced by the copolymer prepared in Comparative Example 3.

[0054] Application Example 6 Compared with Application Example 1, the difference is that the aromatic heterocyclic block polyether ester-polyphenylene sulfide copolymer prepared in Example 1 is replaced by the copolymer prepared in Comparative Example 4.

[0055] Application Example 7 Compared with Application Example 1, the difference is that the modified graphene oxide is changed to ordinary graphene oxide.

[0056] Performance Testing The coatings prepared in corresponding examples 1 to 7 were coated on the surface of a low-carbon steel plate with a thickness of 1 mm and left to stand for 48 hours to form a coating. The bonding strength test was carried out with reference to DL / T693-1999, the impact resistance test was carried out with reference to GB / T 9286-1198, the acid resistance test was carried out with reference to GB / T 1763-1979, the alkali resistance test was carried out with reference to GB / T 1763-1979, the salt spray resistance test was carried out with reference to GB / T1771-2007, and the chemical resistance test was carried out with reference to GB / T1736-1989. The results are shown in Table 1.

[0057] Table 1 Performance test results

[0058] From the above performance test results, it can be seen that the coating formed in Application Example 1 has high toughness and impact resistance, excellent chemical corrosion resistance and bonding performance, especially the comprehensive performance of Application Example 2 is the most outstanding, which is mainly because the aromatic heterocyclic block polyether ester-polyphenylene sulfide copolymer obtained by hydroxyl-terminated aromatic heterocyclic block polyether ester and amino-terminated polyphenylene sulfide has excellent performance. The remaining application examples are significantly worse than the embodiments in the corresponding performance tests because they do not adopt the necessary technical solutions, which better proves the irreplaceable nature of the specific technical solutions of this application in achieving technical effects and solving technical problems.

[0059] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a functionalized aromatic heterocyclic block polyether ester-polyphenylene sulfide copolymer, characterized in that: The following steps are involved: (1) mixing a sulfur source, an alkali metal compound, a polymerization agent, an organic solvent and water to obtain a mixture, stirring and heating the mixture, then adding p-dichlorobenzene to polymerize, and then adding p-aminochlorobenzene to cap the mixture to obtain amino-capped polyphenylene sulfide; (2) under nitrogen protection, polyethylene glycol and 2,5-furandicarboxylic acid are mixed, and then tetraisopropyl titanate is added, and the temperature is raised to react to obtain a hydroxyl-terminated aromatic heterocyclic block polyether ester; (3) Under nitrogen protection, amino-terminated polyphenylene sulfide, hydroxyl-terminated polyether ester, tetrakistriphenylphosphine palladium and toluene are mixed, and the pH is adjusted to 8-11 to obtain an aromatic heterocyclic block polyether ester-polyphenylene sulfide copolymer.

2. The method for preparing the functionalized aromatic heterocyclic block polyether ester-polyphenylene sulfide copolymer according to claim 1, characterized in that: In step (1), the sulfur source is one or more of sodium hydrosulfide, sodium sulfide, and potassium sulfide; And / or, in step (1), the alkali metal compound is sodium hydroxide; And / or, in step (1), the organic solvent is n-methylpyrrolidone; And / or, in step (1), the polymerization agent is sodium acetate.

3. The method for preparing the functionalized aromatic heterocyclic block polyether ester-polyphenylene sulfide copolymer according to claim 1, characterized in that: In step (1), the equivalent ratio of the sulfur source to the alkali metal compound is 1:(0.8-1.5); And / or, in step (1), the equivalent ratio of the sulfur source to the organic solvent is 1:(2-5), and the equivalent ratio of the organic solvent to water is 0.5:(0.85-1.5); And / or, in step (1), the equivalent ratio of the sulfur source to the polymerization agent is 1:(0.02-0.07); And / or, in step (1), the equivalent ratio of the sulfur source, p-dichlorobenzene and p-aminochlorobenzene is 1:(1.2-1.5):(0.3-0.6); And / or, in step (1), the stirring and heating temperature is 150-190° C., and the stirring and heating time is 10-30 min; And / or, in step (1), the polymerization temperature is 210-250° C., and the polymerization time is 2-4 h; And / or, in step (1), the end-capping temperature is 230-270° C., and the end-capping time is 0.5-1 h.

4. The method for preparing the functionalized aromatic heterocyclic block polyether ester-polyphenylene sulfide copolymer according to claim 1, characterized in that: In step (2), the number average molecular weight of the polyethylene glycol is 200-2000; And / or, in step (2), the mass ratio of the polyethylene glycol, 2,5-furandicarboxylic acid and tetraisopropyl titanate is 1:(0.8-1.5):(0.01-0.05).

5. The method for preparing the functionalized aromatic heterocyclic block polyether ester-polyphenylene sulfide copolymer according to claim 1, characterized in that: In step (2), the temperature of the temperature-raising reaction is 180-260° C., and the time of the temperature-raising reaction is 2-5 hours.

6. The method for preparing the functionalized aromatic heterocyclic block polyether ester-polyphenylene sulfide copolymer according to claim 1, characterized in that: In step (3), the mass ratio of the amino-terminated polyphenylene sulfide, the hydroxyl-terminated polyether ester, tetrakistriphenylphosphine palladium and toluene is 1: (1.2-1.5): (0.01-0.05): (1-10).

7. The method for preparing the functionalized aromatic heterocyclic block polyether ester-polyphenylene sulfide copolymer according to claim 1, characterized in that: In step (3), the reaction temperature is 80-110° C., and the reaction time is 4-8 h.

8. An aromatic heterocyclic block polyether ester-polyphenylene sulfide copolymer obtained by the preparation method of the functionalized aromatic heterocyclic block polyether ester-polyphenylene sulfide copolymer as claimed in any one of claims 1 to 7.

9. A PPS coating, characterized in that: The coating comprises the following components by mass ratio: 100 parts of the aromatic heterocyclic block polyether ester-polyphenylene sulfide copolymer obtained by the preparation method of the functionalized aromatic heterocyclic block polyether ester-polyphenylene sulfide copolymer according to any one of claims 1 to 7 or the aromatic heterocyclic block polyether ester-polyphenylene sulfide copolymer according to claim 8; and 1-3 parts of nano filler.

10. The PPS coating according to claim 9, characterized in that: The nanofiller is modified graphene oxide, and the preparation method of the modified graphene oxide is as follows: Dissolve graphene oxide in water, ultrasonicate for 1-2 hours, then add urea, the mass ratio of urea to graphene oxide is (4-8):1, reflux at 60-100°C for 0.5-1.5 hours, wash and dry to obtain modified graphene oxide; The particle size of the graphene oxide is 50-100 nm.

Citation Information

Patent Citations

  • Heat resistant anticorrosive composite polyphenylene sulfide epoxy paint and its preparation method

    CN100402617C

  • Polyphenylene sulfide compound coating and preparation method thereof

    CN114989721A